RECORDING GLOBAL VOICES: SYSTEMATIC LITERATURE REVIEW IN PATIENT SAFETY CULTURE SURVEYS - Yanuar Jak; Santi Anugrahsari (Universitas Airlangga, 2025)
Background: Measurement of patient safety culture is often conducted using various questionnaire methods and multiple respondents. Patient safety culture cannot be ignored; therefore, understanding these results is crucial for further study. Aim: To investigate the results of measuring patient safety culture in hospitals across various countries. Method: This study is a systematic literature review of articles published between 2013 and 2023. The selection process followed the PRISMA, which included identification, screening, eligibility, and inclusion. Selected articles were evaluated for quality, and the data were then analyzed thematically to identify instruments, approaches, and challenges in measuring patient safety culture. Results: The systematic review identified 45 relevant studies. The HSOPSC instrument was the most widely used, followed by the SAQ and the PSFHI, with varying local adaptations. The analysis revealed challenges with instrument reliability, differences in cultural contexts, and resource limitations. These findings promoted standardization and local adaptation in measuring patient safety culture. Conclusion: After 24 years of global recognition of patient safety, this study confirms that measuring patient safety culture is a strategic pillar in hospital quality improvement. This finding has academic and practical values, supporting cultural improvement strategies and evidence-based patient safety policies. Keywords: Doctor, Hospital Community, Hospital, Nurse, Patient Safety Culture